2012
DOI: 10.1111/j.1365-2486.2012.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Net ecosystem exchange modifies the relationship between the autotrophic and heterotrophic components of soil respiration with abiotic factors in prairie grasslands

Abstract: We investigated the relationships of net ecosystem carbon exchange (NEE), soil temperature, and moisture with soil respiration rate and its components at a grassland ecosystem. Stable carbon isotopes were used to separate soil respiration into autotrophic and heterotrophic components within an eddy covariance footprint during the 2008 and 2009 growing seasons. After correction for self-correlation, rates of soil respiration and its autotrophic and heterotrophic components for both years were found to be strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
93
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 125 publications
10
93
1
4
Order By: Relevance
“…3). The contributions of each subcomponent to R eco varied within a similar range as reported previously (Gomez-Casanovas et al, 2012;Hu et al, 2008;Li et al, 2013;Luo and Zhou, 2006;Savage et al, 2013;Zhou et al, 2007). Our results indicate that warming eventually could cause R eco to become dominated by R plant , an idea that has been suggested in previous studies (Hicks Pries et al, 2015;Peng et al, 2014;Suseela and Dukes, 2013).…”
Section: The Effects Of Warming On the Contributions Of Ecosystem Ressupporting
confidence: 76%
“…3). The contributions of each subcomponent to R eco varied within a similar range as reported previously (Gomez-Casanovas et al, 2012;Hu et al, 2008;Li et al, 2013;Luo and Zhou, 2006;Savage et al, 2013;Zhou et al, 2007). Our results indicate that warming eventually could cause R eco to become dominated by R plant , an idea that has been suggested in previous studies (Hicks Pries et al, 2015;Peng et al, 2014;Suseela and Dukes, 2013).…”
Section: The Effects Of Warming On the Contributions Of Ecosystem Ressupporting
confidence: 76%
“…difficult for satellite technology to monitor various respiratory processes, especially those in the soil (Valentini et al, 2000;Running et al, 2004;Olofsson et al, 2008;Xiao et al, 2008;Tang et al, 2012), which limit the application of remote sensing data in R e estimation. However, R e showed close relationships with easily satellite-retrieved GPP (e.g., Knohl et al, 2005;Tang et al, 2005;Moyano et al, 2007Moyano et al, , 2008Larsen et al, 2007;Bahn et al, 2008;Gomez-Casanovas et al, 2012;Huang and Niu, 2013) and temperature (e.g., Lloyd and Taylor, 1994;Frank et al, 2002;Reichstein et al, 2003;Bond-Lamberty and Thomson, 2010) in most of ecosystems, and upon these relationships some empirical or semi-empirical satellite-driven R e models were developed and validated at the plot or regional scale (Vourlitis et al, 2003;Gilmanov et al, 2005;Rahman et al, 2005;Schubert et al, 2010;Jägermeyr et al, 2014). However, extensive studies reported that the responses to GPP and temperature varied among the R e components (e.g., Gaumont-Guay et al, 2008;Kuzyakov and Gavrichkova, 2010), and the current satellite-driven R e models almost all neglected these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, RS is one of the major contributors to the carbon balance, and small changes in RS rate could give rise to significant changes in atmospheric CO2 concentration, leading to feedbacks to climate change (Ryan & Law 2005). Although the significance of RS for carbon balance on a regional and even the global scale has been demonstrated, there is still much to understand about biotic or abiotic controllers of RS and its source components (Gomez-Casanovas et al 2012). For example, partitioning RS is still challenging because of remarkable soil disturbances (Hanson et al 2000, Tang et al 2005.…”
mentioning
confidence: 99%